Peran Budaya Lokal dalam Pembentukan Gaya Bahasa Remaja di Media Sosial - Nadya Kartika; Rozi Sakhbana Hasibuan; Sikni Sari Siagiaan (Jurnal Psikotes, 2026)
This study aims to analyze the role of local culture in shaping adolescents’ language styles on social media through a literature review approach. The research focuses on examining the role of local values, norms, and forms of cultural expression in shaping adolescents’ communication patterns across various digital platforms, such as Instagram, TikTok, and X (formerly Twitter). The research method employed is a literature review, involving the examination of various scholarly sources, including books, journal articles, and previous studies relevant to the fields of sociolinguistics, cultural studies, and digital media. The findings indicate that local culture plays a significant role in shaping adolescents’ language styles on social media. This role is reflected in lexical choices, the use of slang, and the adaptation of region-specific expressions that have evolved into popular linguistic forms among young users. Social media serves as a strategic space for adolescents to construct and negotiate their cultural identities while simultaneously expanding the presence of local languages within the context of modern communication. Therefore, this study is expected to contribute to the development of sociolinguistic scholarship and to enhance understanding of the dynamics of local culture amid the growth of contemporary digital culture.